Flags over the Maghreb: Chronological Clues and Political Symbolism in Portolan Charts. - Robles Macías, Luis A. (Imago Mundi, 2025)
Portolan charts of the Mediterranean never depicted political boundaries as lines, but they sometimes used flags to indicate the possession of selected cities. Historians have observed that these emblems tend to be accurate in shape and colour but in general unreliable to date charts until recently, when it has been suggested that flags located in the Maghreb region could be useful in this way. This article assesses the potential of Maghreb flags as a dating tool and addresses the broader questions of which mapmakers drew flags in the Maghreb, when and why. For this purpose, the author surveyed around three quarters of extant portolan charts and atlases and built and statistically analysed a database of Maghreb flags. The article offers insights about which mapmaking centres and authors privileged the use of flags, and the reasons why they sometimes were not chronologically accurate. It presents a methodology to date charts based on Maghreb flags, quantifying its reliability and applying it to almost a hundred undated works. Furthermore, it shares how flagged portolan charts turn out to provide rare glimpses into their authors' knowledge and opinions about the struggle for the Maghreb.